DCDC2 Mutations Cause Neonatal Sclerosing Cholangitis. Issue 10 (24th August 2016) - Girard, Muriel; Bizet, Albane A.; Lachaux, Alain; Gonzales, Emmanuel; Filhol, Emilie; Collardeau‐Frachon, Sophie; Jeanpierre, Cécile; Henry, Charline; Fabre, Monique; Viremouneix, Loic; Galmiche, Louise; Debray, Dominique; et al.
Abstract : For the first time we report DCDC2 mutation in patients with Neonatal Sclerosing Cholangitis. DCDC2 mutations impair the localization of the protein in cholangiocytes which is absent in cilia and accumulated in cytoplasm. ABSTRACT: Neonatal sclerosing cholangitis (NSC) is a rare biliary disease leading to liver transplantation in childhood. Patients with NSC and ichtyosis have already been identified with a CLDN1 mutation, encoding a tight‐junction protein. However, for the majority of patients, the molecular basis of NSC remains unknown. We identified biallelic missense mutations or in‐frame deletion in DCDC2 in four affected children. Mutations involve highly conserved amino acids in the doublecortin domains of the protein. In cholangiocytes, DCDC2 protein is normally located in the cytoplasm and cilia, whereas in patients the mutated protein is accumulated in the cytoplasm, absent from cilia, and associated with ciliogenesis defect. This is the first report of DCDC2 mutations in NSC. This data expands the molecular spectrum of NSC, that can be considered as a ciliopathy and also expands the clinical spectrum of the DCDC2 mutations, previously reported in dyslexia, deafness, and nephronophtisis.